Aneuploidy Mechanisms in Human Colorectal Preneoplastic Lesions and Barrett’s Esophagus. Is There a Role for K-Ras and p53 Mutations? - Walter Giaretti (Analytical Cellular Pathology)
The link of aneuploidy and heteroploidy in human solid tumours with early genetic events is poorly understood. The study of human preneoplastic precursor lesions, i.e., colorectal adenomas, chronic ulcerative colitis lesions, and Barrett’s esophagus, as considered in this review, appears particularly useful to achieve this aim. Literature data examined here on aneuploidy were obtained by image and flow cytometry, classical cytogenetics, and in situ hybridization based cytogenetics. It appears that aneuploidy is linked with specific gene mutations, i.e., of the tumour suppressor gene p53 in chronic ulcerative colitis and in Barrett’s esophagus, and of the protooncogene K‐ras in colorectal adenomas. These data and data from experiments using in vitro and mouse models, suggest that chromosome instability, tetraploidization, and asymmetrical chromosome segregation during cell division are the result of deregulated cell cycle genes with multiple functions that normally exert active checks on the cell cycle processes including apoptosis and chromosome stability.